Judgments of a Product’s Quality and Perceptions of User Experience Can Be Mediated by Brief Messaging That Matches the Person’s Pre-existing Attitudes - Walker, Ian; Thomas, Gregory O.; Natarajan, Sukumar; Holt, Nigel (Frontiers in Psychology, 2020)
The mediation of an attitude to a product following a brief message is investigated. Statements indicating whether a computer was running on energy from renewable or more conventional sources were presented and users’ experiences were measured. Participants’ pre-existing environmental concern and the satisfaction they expressed with the computers were related, but only when the ‘renewable energy’ message was presented. We conclude that enduring attitudes to environmental concern and situation-specific knowledge can interact in evaluations of a situation – a finding with implications for behavior-change strategies. Theoretically, results are discussed in terms of ‘spillover’ from one behavior to another, the Halo Effect and self-activation, where those with a self-identity of being environmentally conscious have this identity activated by messaging congruent with their self-identity, resulting in an influence of their opinion of a product.